Perceived Impact of Financial Assistance Program on Retaining Vulnerable Children in Lesotho’s Secondary Schools - Mohoebi, Matseliso Alice; Khanare , Fumane Portia (CV. Literasi Indonesia, 2025)
Following the high influx of learners in primary schools due to the Education For All (EFA) policy, many learners could not access secondary education because of the high costs of tuition fees and other hidden costs. In response to this, the Lesotho government introduced several financial assistance strategies to narrow the gap between primary and secondary education. The paper focused on the Lesotho government's financial assistance programs (FAP) to increase access for learners from poor socio-economic backgrounds and the factors that make it difficult for such learners to complete secondary education. We used a rational approach as a theoretical framework to unravel the contextual conditions of FAP and their impact on retaining OVC in schools. The paper was lensed under the interpretivism paradigm and designed using qualitative research, relying on the case study of one school in the poor area of Lesotho. Using the purposive sampling method, one principal and two teachers were selected in a secondary school and engaged in semi-structured interviews. The paper employed thematic analysis to derive themes and trends that emerged from the data. The findings point to poor contextual conditions, such as OVC socioeconomic backgrounds, resources, and other social issues, which did not address the deeper problems of OVC in accessing and completing their education. The paper concludes that for this FAP to have a lasting and meaningful impact on OVC in accessing secondary schooling, they need to thoroughly review their objectives to fully address the needs of OVC in and outside school.